Senior high school students in Ghana and their labor market aspirational Gap - KENNEDY ACHEAMPONG (Jurnal Pendidikan Ilmu Sosial, 2023)
This study aimed to identify the variables affecting senior high school students (SHS 3) labor market aspirations in Ghana. This investigation was led by a quantitative paradigm. A simple random sampling approach of 445 SHS students was sampled for the study. In this study, a questionnaire was utilized.  To analyze the data, the main statistical tools employed were percentages, and contingency coefficients using IBM SPSS version 26.  From the finding of the study, it appears that students' demographic traits have a direct bearing on their labor market aspirations.  Moreover, the majority of SHS 3 students are drawn to the public sector, even though different demographic factors influence both the sort of work that students want to pursue and the economic sector in which they want to work. Furthermore, SHS students are not drawn to some of Ghana's most pressing labor demands. The implications of the findings and practical considerations are discussed in the study.